Development of dense Al2O3–TiO2 ceramic composites by the glass-infiltration of porous substrates prepared from mechanical alloyed powders - Alves, Manuel F.R.P.; Santos, Claudinei dos; Cossu, Caio M.F.A.; Suzuki, Paulo A.; Ramos, Alfeu S.; Ramos, Erika C.T.; Simba, Bruno G. [UNESP]; Strecker, Kurt (Elsevier, 2020)
In this work bio-composites were obtained by infiltrating porous alumina–titania (Al2O3–TiO2) substrates with a lanthania-rich (La2O3) glass. Al2O3–TiO2 substrates were fabricated using high-energy milled powder mixtures of two different compositions with molar ratios of 3:1 and 1:1, uniaxial compaction under 100 MPa and sintering at 1300 °C - 2 h or 1400 °C - 2 h. The high energy milling process of the powders resulted in homogeneous, extremely fine mixtures. For comparison, as-received Al2O3 and TiO2 powders were also mixed at a proportion of 3:1 and sintered at 1600 °C - 2 h. The sintered substrates presented α-Al2O3 and β-Al2TiO5 (aluminium titanate) as crystal phases and relative densities ranging between 65.5 ± 2% and 69.4 ± 1.2% of the theoretical density. These porous substrates were infiltrated with a lanthania containing glass at a temperature of 1140°C-2h. The resulting ceramic composites exhibited high density, varying between 94 to 99% of the theoretical density, Vickers hardness ranging between 895 ± 14 HV and 1036 ± 33 HV, fracture strength ranging between 218 ± 28 MPa and 254 ± 18 MPa and a fracture toughness (KC) higher than 2.6 MPam1/2. Phase analysis of the infiltrated substrates by X-ray diffraction indicated the decomposition of aluminium titanate into alumina and titania besides the formation of lanthanum borosilicate, LaBSiO5. In addition, all compositions studied presented non-cytotoxic behaviour and low chemical solubility, inferior to 75 μg/cm2.
Keywords: Alumina-titania composite; Glass infiltration; Mechanical properties